Dirichlet-Type Problems for Systems of Partial Differential Equations Unresolved with Respect to the Highest Time Derivative - Bilusyak, N.I.; Komarnyts'ka, L. I.; Ptashnik, B. I. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We establish conditions for the correct solvability of problems for systems of partial differential equations unresolved with respect to the highest time derivative with Dirichlet-type conditions with respect to time and periodic conditions with respect to space variables. We prove metric theorems on lower bounds for small denominators appearing in the course of the solution of these problems.